Conhecimento e competências no trabalho e na escola - Zeneida Kuenzer, Acacia (Boletim Técnico do Senac, 2002)
This article, based on field studies performed at Petrobrás’ Presidente Getúlio Vargas Refinery, located in the greater Curitiba area, and on the theoretical and activities categories, proposes to discuss Perronoud’s claim, incorporated by the national guidelines for basic and professional education, that competencies are developed in school. To do so, it takes the praxis category to show that theoretical work and practical activity, while articulated, maintain specificities that allow a distinction between different spaces and practises for their development.